Cerebrovascular Risk-Factors of Prevalent and Incident Brain Infarcts in the General Population: The AGES-Reykjavik Study. Issue 4 (23rd November 2021) - Sigurdsson, Sigurdur; Aspelund, Thor; Kjartansson, Olafur; Gudmundsson, Elias; Jonsson, Palmi V.; van Buchem, Mark A.; Gudnason, Vilmundur; Launer, Lenore J.
Abstract : Background: Studies on the association of cerebrovascular risk factors to magnetic resonance imaging detected brain infarcts have been inconsistent, partly reflecting limits of assessment to infarcts anywhere in the brain, as opposed to specific brain regions. We hypothesized that risk-factors may differ depending on where the infarct is located in subcortical-, cortical-, and cerebellar regions. Methods: Participants (n=2662, mean age 74.6±4.8) from the longitudinal population-based AGES (Age, Gene/Environment Susceptibility)-Reykjavik Study underwent brain magnetic resonance imaging at baseline and on average 5.2 years later. We assessed the number and location of brain infarcts (prevalent versus incident). We estimated the risk-ratios of prevalent (PRR) and incident (IRR) infarcts by baseline cerebrovascular risk-factors using Poisson regression. Results: Thirty-one percent of the study participants had prevalent brain infarcts and 21% developed new infarcts over 5 years. Prevalent subcortical infarcts were associated with hypertension (PRR, 2.7 [95% CI, 1.1–6.8]), systolic blood pressure (PRR, 1.2 [95% CI, 1.1–1.4]), and diabetes (PRR, 2.8 [95% CI, 1.9–4.1]); incident subcortical infarcts were associated with systolic (IRR, 1.2 [95% CI, 1.0–1.4]) and diastolic (IRR, 1.3 [95% CI, 1.0–1.6]) blood pressure. Prevalent and incident cortical infarcts were associated with carotid plaques (PRR, 1.8 [95% CI, 1.3–2.5] and IRR, 1.9 [95% CI, 1.3–2.9], respectively), and atrial fibrillation was significantly associated with prevalent cortical infarcts (PRR, 1.8 [95% CI, 1.2–2.7]). Risk-factors for prevalent cerebellar infarcts included hypertension (PRR, 2.45 [95% CI, 1.5–4.0]), carotid plaques (PRR, 1.45 [95% CI, 1.2–1.8]), and migraine with aura (PRR, 1.6 [95% CI, 1.1–2.2]). Incident cerebellar infarcts were only associated with any migraine (IRR, 1.4 [95% CI, 1.0–2.0]). Conclusions: The risk for subcortical infarcts tends to increase with small vessel disease risk-factors such as hypertension and diabetes. Risk for cortical infarcts tends to increase with atherosclerotic/coronary processes and risk for cerebellar infarcts with a more mixed profile of factors. Assessment of risk-factors by location of asymptomatic infarcts found on magnetic resonance imaging may improve the ability to target and optimize preventive therapeutic approaches to prevent stroke.